Generation and characterisation of a tomato epigenetic recombinant inbred line (epiRIL) population - Kuswandi, Paramita Cahyaningrum (2019)
Heritable changes in gene expression, which are not due to alterations in the DNA sequence, are termed epigenetic modifications and they play an important role in plant development (Pickaard and Scheid, 2014). These changes include those in DNA methylation, chromatin remodelling and levels of small RNAs. This project focuses on the effects of variations in DNA methylation on the cultivated tomato (Solanum lycopersicum).